Proximity to chronic wasting disease, perceived risk, and social trust in the managing agency. Issue 2 (4th March 2018) - Vaske, Jerry J.; Miller, Craig A.; Ashbrook, Alexa L.; Needham, Mark D.
ABSTRACT: This article examined relationships between proximity to chronic wasting disease (CWD) and perceived risk and trust. The sample included 1, 606 hunters in one of 10 northern Illinois counties with CWD, 1, 958 hunters in a non-CWD county adjacent to these counties with CWD, and 2, 099 hunters from the remaining non-CWD counties in Illinois. Compared to hunters in non-CWD counties, those in CWD counties were hypothesized to: (a) perceive more risk of CWD to humans, (b) perceive more risk of CWD to deer, (c) report less trust in the Illinois Department of Natural Resources (IDNR) CWD information, and (d) have less trust in the IDNR management of CWD. The first two hypotheses were not supported, as hunters in CWD counties perceived less risk to humans and deer than did respondents in non-CWD counties. Hunters in CWD counties, however, were less trusting of the IDNR information and management compared to the other hunters.